Clinicopathological correlation of polypoidal choroidal vasculopathy revealed by ultrastructural study. Issue 10 (1st October 2002) - Okubo, A; Sameshima, M; Uemura, A; Kanda, S; Ohba, N
Abstract : Aims: To describe the clinical and histopathological findings in a patient with polypoidal choroidal vasculopathy. Methods: A 76 year old Japanese man had a discrete, orange-red lesion of 1 disc diameter in the macula, with the fluorescein and indocyanine green angiographic and optical coherence tomographic findings compatible with polypoidal choroidal vasculopathy. He underwent a surgical removal of the macular lesion, followed by light and electron microscopic examinations. Results: The histopathological examination revealed that the specimen consisted of degenerated retinal pigment epithelium-Bruch's membrane-choriocapillaris complex and inner choroid. A tortuous, unusually dilated venule was present adjacent to an arteriole with marked sclerotic changes, appearing to form arteriovenous crossing. These vessels seemed to represent native inner choroidal vessels, and had haemorrhage per diapedesis. Blood cells and fibrin filled the lumina of the vessels and accumulated in the extravascular spaces, indicating vascular stasis. Conclusion: Hyperpermeability and haemorrhage due to stasis of a dilated venule and an arteriole involved by sclerosis at the site where they cross in the inner choroid might cause oedema and degeneration of the tissue. Voluminous accumulation of blood cells and fibrin might generate elevation of tissue pressure sufficient to displace the weakened lesion anteriorly. The result suggests that the polypoidal vessels in this case represent abnormality in the inner choroidal vasculature.